UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN SERAI WANGI (Cymbopogon nardus L.) UNTUK MENGENDALIKAN PENYAKIT ANTRAKNOSA PADA BUAH CABAI MERAH PASCA PANEN - YETTI ELFINA; MUHAMMAD ALI; MORINA CHRONIKA TAMPUBOLON (Jurnal Sagu, 2016)
The research aims to observe and obtain a better concentration of powder extract citronella grass leaf tocontrol anthracnose disease on red chili fruits. The research has been conducted experimentally using acompletely randomized design, consisted of 6 treatments and 4 replications thus obtained 24 trial units. Theresearch consisted of two phases: in vitro inhibition of C. capsici and in vivo application of powder extractcitronella grass leaf on red chili fruits. The concentration of powder extract citronella grass leaf used are:S0= 0 g/l, S1= 50 g/l, S2= 100 g/l, S3= 150 g/l, S4= 200 g/l dan S5= 250 g/l of water. The data werestatistically analyzed using analysis of variance and the means were tested with Duncan ‘s New MultipleRange Test (DNMRT) at level of 5%. The results of the research showed that the concentration of powderextract citronella grass leaf at 200 g/l of water tended to show a better ability to inhibit the growth of C.capsici at in vitro phase with growth inhibition up to 22,26%.Key words: Red chili, C. capsici and Cymbopogon nardus L.